Evaluating E-Administration Features on User Satisfaction Using the Kano Model: A Melung Village-Owned Enterprise Case Study - Albana, Ilham; Ihsan, Imamul; Firnandri, Yerikho Putra (Universitas Bina Darma, 2024)
This research evaluates user satisfaction with the e-administration system at the Village-Owned Enterprises (BUMDes) Melung, focusing on identifying features that influence user satisfaction using the Kano model. A survey was conducted with 50 respondents who are active users of the system, analyzing 16 key features, including user registration, online payment, financial transparency, and service reporting. The results indicate that the Online Payment and Financial Transparency features are categorized as